The essential differences in microbial and chemical components of musk of different qualities secreted by captive male forest musk deer (Moschus berezovskii). Issue 6 (31st January 2022) - Wang, Yan; Sun, Mao; Chang, Fan; Wang, Jun; Wang, Yan; Tang, Jie; Zhang, Kun; Gao, Lei; Xue, Xiaochang; Wan, Yi
Summary: Musk is a precious raw material and ingredient in Chinese traditional medicine. The production of unqualified musk has become a puzzling problem in forest musk deer (FMD) breeding. However, what the essential differences between so‐called unqualified musk and mature qualified musk have not yet been elucidated. In this study, 12 musk samples were collected and separated into two groups according to their external properties. One group is white or black cream‐like secretion with sour or unpleasant odour (MM); the other group is brown or blackish brown solid secretion with pleasant fragrance (DM). Next‐generation sequencing and gas chromatography‐mass spectrometry were used to explore the essential differences between the DM and MM groups in microbial and chemical compositions. The results indicate that the DM group has more heterogenous microbial structure but simpler relationships among microbial communities. LEfSe analysis showed that 14 taxa at the genus level could be used to distinguish the DM and MM groups and Bacillus, Paracoccus, tenoteophomonas, Mycobacterium and Leuconostoc were more abundant in the DM group ( P  < 0.05). In addition, six compounds were identified to specifically distinguish the DM and MM groups under the OPLS‐DA model. PICRUSt analysis revealed that metabolic pathways such as carbohydrate metabolism, nucleotide metabolism, energy metabolism, transport and catabolism were enriched in the DM group. All these findings of differences in microbiota and chemical compositions would provide potential clues for MM quality improvement and new evidence for the scientific establishment of a quality evaluation standard for musk. Abstract : Next‐generation sequencing and gas chromatography‐mass spectrometry were used to explore the essential differences between different quality of musk in microbial and chemical compositions. The results indicate that 14 taxa at the genus level and six compounds were identified to specifically distinguish DM and MM groups under the LEfSe analysis and OPLS‐DA model. All these findings of differences in microbiota and chemical compositions would provide potential clues for MM quality improvement and new evidence for the scientific establishment of a quality evaluation standard for musk.